Minyak Kelapa Beraditif Minyak Zaitun sebagai Isolasi Peralatan Tegangan Tinggi - Moch. Dhofir; Nur Rahma Dona; Unggul Wibawa; Rini Nur Hasanah (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2017)
This paper discusses the improvement of dielectric strength of dielectric coconut oil using olive oil to be used as an alternative to liquid insulation on high voltage equipments. Increasing the breakdown voltage level has been done by adding olive oil of 5% -25% into coconut oil. Heating was considered to reduce the water content in coconut oil. Electrical testing (using breakdown voltage test), physical testing (by testing the water content using oven method), and analysis of the acid content of simple saturated fat using mixing formula, have been performed to determine the feasibility of coconut oil as insulation agent. The test results indicated the breakdown voltage of a pure coconut oil value of 23.47kV / 2.5mm, which did not fulfilled the IEC 156 standard, which is 30kV/2.5mm. The addition of olive oil could increase the breakdown voltage level to 38.73 kV / 2.5 mm and if the heating can reach 51.15kV/2.5mm. The highest breakdown volatge level of 54.01kV/ 2.5mm could be obtained by mixing the olive oil and heating the coconut oil at once. ell. It can be concluded that the addition of olive oil could decrease the saturated fatty acid content from 91% to 72.2%, whereas the heating could reduce the water content from 2697 ppm to 361 ppm. From the point of view of water content, the modified coconut oil could not meet the maximum permitted standard JIS 2320, which is 50 ppm. Based on the achieved breakdown voltage level, the considered coconut oil will be able to work on electrical equipment with a working voltage level of 0.75 kV-13.2 kV.